Analisis Peran Auditor KAP Buntaran dan Lisawati dalam Pencatatan Jurnal Penyesuaian Pembetulan PPh Pasal 21 - Pratama, Alzena Alifia Meigita; Habibi, M. Luthfillah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine the role of auditors in financial statements and recording of tax reporting of client companies when conducting the audit process. The research method used is a descriptive qualitative method, with primary data collection from interviews with members of the KAP Buntaran Lisawati auditor team on duty. The results show that the client company has fulfilled its tax obligations in reporting and withholding Income Tax Article 21, but it was found that there was a calculation error that required the company to make tax corrections. The auditor will record an adjustment journal of the correction of Income Tax Article 21, if the client company has met the requirements of the correction of Income Tax Article 21 and pays the tax from the recalculation in accordance with applicable regulations. Companies are given their respective responsibilities in their tax compliance independently, therefore it is necessary to be precise in calculating tax burdens before conducting tax reporting.